A CLOSER LOOK AT HOW AND WHEN FAMILY-SUPPORTIVE SUPERVISION INFLUENCE WORK INTERFERENCE WITH FAMILY: THE ROLES OF FAMILY-ROLE OVERLOAD AND TASK CRAFTING - Walumbwa, Fred O.; Christensen-Salem, Amanda; Babalola, Mayowa T.; Kasimu, Paul; Garba, Omale A.; Guo, Liang (The International Journal of Human Resource Management, 2021)
Although family–supportive supervision (FSS) has been identified as one of the most useful social resources for reducing the occurrence of work interference with family (WIF), relatively little is known about the boundary conditions and the underlying mechanisms through which this relationship occurs. Drawing on conservation of resources (COR) theory, we examined how and when FSS relates to WIF in two field studies, focusing on family–role overload as a moderator and employee task crafting as a mediator. Results from Study 1, using multi-wave data from a high-technology firm, showed that family role–overload moderated the relationship between FSS and WIF such that the relationship was stronger for employees with more family role–overload than for those with less family role–overload. Results from Study 2, using multi-wave data from employees working in different industries, revealed that employee task crafting mediated the interactive effect of FSS and family–role overload on WIF. Implications of these findings for research and practice are discussed.
Keywords: Type of access: Open Access; Family–supportive supervision; work interference with family; family–role overload